PERILAKU MASYARAKAT TERHADAP FENOMENA PROSTITUSI DI JALAN BUNG TOMO, DESA PEMECUTAN KAJA, KOTA DENPASAR - Dewi, Ni Kadek Trisna; Zuryani, Nazrina; Krisna Aditya, I Gst. Ngr. Agung (JURNAL ILMIAH SOSIOLOGI: SOROT, 2023)
Sociological research analyzing community behavior towards Commercial Sex Workers (CSWs) activities is very minimal. This descriptive-explanatory qualitative research examines the phenomenon of prostitution in the Bung Tomo Street area, Denpasar City. The perspective of an individual as a member of society is explored to answer the phenomenon of prostitution in the research location in Banjar Kusuma Jati, Denpasar City. The Behavior Theory from Lawrence Green is used to dissect predisposing factors, enabling factors, and reinforcing factors. The community residing in Bung Tomo Street has a demographic awareness of the impact of prostitution practices. There are services users as a enabling factors who reside across Bung Tomo Street and some traders who feel benefited. The reinforcing factors on the phenomenon of prostitution in Bung Tomo Street are related to the accepting community. The behavior of the community that is against the phenomenon of prostitution and concerns about the transmission of HIV/AIDS become the reason for community rejection. Therefore, the opposing community then reports to the village apparatus.The community still expects the Satuan Polisi Pamong Praja (Satpol PP) and Social Service to carry out rehabilitation programs. It is suggested that both customary and official apparatus together with the community in the area of Bung Tomo street increase the education and communication in the area under study. The community can increase literacy related to the dangers of the spread of HIV/AIDS and be more alert on the behaviour of young generation towards CSWs. Keywords: Community behavior, prostitution, Bung Tomo street